Professionalization of VET Teachers and Lecturers and Practices in TVET Institutions in an International Perspective - Grollmann, Philipp [Verfasser] (My University, 2009)
"This chapter analyses the different factors exerting an influence on the professional knowledge, practices and the performance of teaching staff involved in technical and vocational education and training (TVET). In addition to teacher education, which is a crucial lever for increasing the quality of teachers and their professional performance, the institutions in which teachers work constitute another crucial factor shaping the quality of their provision. Therefore, the institutional environments are held not just as independent variables, but are also closely interconnected with teachers' professional practice. This means that any reform trying to professionalize TVET - wether on the global or local level - needs to take into account both levers." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2.3 Lehrer; G 1.2.3.2 Anforderungen & Bedarfe; Berufsbildung; Lehrer; Professionalisierung; Lehrerbildung; Berufsbild; Anforderungsprofil; Interkulturelle Faktoren